STUDENT CENTERED; PARADIGMA BARU INOVASI PEMBELAJARAN - Wijayanti, Wiwik (MAJALAH ILMIAH PEMBELAJARAN, 2011)
School have seemed to proceed as though there were one standard slassroom situation suitable for all students: one textbook, one method, or one curriculum program. School should start with very different assumption that individual students need very different type and qualities of instruction and require various types of aid, such as group study, tutorial help, or variation in instructional materials that range beyond textbooks to acwide variety of printed and audiovisual material, academic games and so on. These are Student Centered Learning, an instruction which suitable for individual different. Another variable is the degree of perserverence of the learner. If he find his effort and feel success in learning, his perserverence increase. Motivation is so important and so complex that teachers are well advised to seek out and employ differentiated teaching techniques tailored to individual student and designed to produce positive results.